Masked Sentence Recognition Assessed at Ascending Target-to-Masker Ratios. Issue 2 (March 2015) - Buss, Emily; Calandruccio, Lauren; Hall, Joseph W.
<x xml:space="preserve">Abstract</x> Objectives: Masked sentence recognition is typically evaluated by presenting a novel stimulus on each trial. As a consequence, experiments calling for replicate estimates in multiple conditions require large corpora of stimuli. The present study evaluated the consequences of repeating sentence-plus-masker pairs at ascending target-to-masker ratios (TMRs). The hypothesis was that performance on each trial would be consistent with the cues available to the listener at the associated TMR, resulting in similar estimates of threshold and slope for procedures using novel versus repeated sentences within an ascending-TMR block of trials. Design: A group of 37 normal-hearing young adults participated. Each listener was tested in the presence of one of three maskers: a multitalker babble, a speech-shaped noise, or an amplitude-modulated speech-shaped noise. There were two data collection procedures, both proceeding in blocks of trials with ascending TMRs. The novel-stimulus procedure used five lists of AzBio sentences, one presented at each of five TMRs, with a novel sentence and masker sample on each trial. The repeated-stimulus procedure used a single list of AzBio sentences, with each sentence presented at multiple TMRs, progressing from low to high; each sentence was paired with a single masker sample, such that only the TMR changed within blocks of repeated stimuli. Listeners completed one run with the novel-stimulus procedure and five runs with the repeated-stimulus procedure. The resulting values of percent correct at each TMR were fitted with a logit function to estimate threshold and psychometric function slope. Results: The novel- and repeated-stimulus procedures resulted in generally similar data patterns. After controlling for effects related to the order in which listeners completed the six data collection runs, mean thresholds were slightly higher (<0.5 dB) for the repeated-stimulus procedure than the novel-stimulus procedure in all three maskers. Function slopes for the multitalker babble and amplitude-modulated noise maskers were slightly shallower using the repeated-stimulus than the novel-stimulus procedure, but slopes were comparable for the speech-shaped noise. The quality of psychometric function fits was significantly better for the repeated-stimulus than the novel-stimulus procedure, even when comparing a single run of the repeated-stimulus procedure (using one list) to a run of the novel-stimulus procedure (using five lists). Conclusions: Repeating sentences at ascending TMRs is an efficient method for estimating thresholds and psychometric function slopes, both in terms of the number of sentences and the number of trials.